2000
DOI: 10.1002/1097-4547(20000615)60:6<725::aid-jnr4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin-3 (NT-3) diminishes susceptibility of the oligodendroglial lineage to AMPA glutamate receptor-mediated excitotoxicity

Abstract: Prior reports demonstrated that cells of the oligodendroglial lineage are susceptible to excitotoxic necrosis mediated by α‐amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionic acid glutamate receptors (AMPA‐GluR), and also showed that these cells express the high affinity neurotrophin receptors, TrkC and TrkA. We now report that: a) oligodendroglial progenitors (OP) and immature oligodendroglia are more vulnerable to AMPA‐GluR‐mediated excitotoxicity than are mature oligodendroglia; b) TrkC expression falls substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Compared with primary OLC cultures with respect to the expression of surface markers and of AMPA-GluR subunits, JS 3/16 OP and ImO correspond to an intermediate phenotype between primary preprogenitors and progenitors, and that between primary progenitors and immature oligodendrocytes, respectively (Grinspan et al, 1990;authors' unpublished observations). Despite these discrepancies in differentiation behavior, JS 3/16 showed similar vulnerability to AMPA-GluR-mediated excitotoxicity as A2B5-immunopanned primary oligodendroglial cultures, in which we observed 33% death of progenitor cells and 57% death of immature oligodendrocytes after a 24-h incubation with AMPAϩCYZ (Kavanaugh et al, 2000). The important advantages of the JS 3/16 cells are homogeneity and ready availability in quantities sufficient for all forms of molecular analysis.…”
Section: Discussionmentioning
confidence: 74%
“…Compared with primary OLC cultures with respect to the expression of surface markers and of AMPA-GluR subunits, JS 3/16 OP and ImO correspond to an intermediate phenotype between primary preprogenitors and progenitors, and that between primary progenitors and immature oligodendrocytes, respectively (Grinspan et al, 1990;authors' unpublished observations). Despite these discrepancies in differentiation behavior, JS 3/16 showed similar vulnerability to AMPA-GluR-mediated excitotoxicity as A2B5-immunopanned primary oligodendroglial cultures, in which we observed 33% death of progenitor cells and 57% death of immature oligodendrocytes after a 24-h incubation with AMPAϩCYZ (Kavanaugh et al, 2000). The important advantages of the JS 3/16 cells are homogeneity and ready availability in quantities sufficient for all forms of molecular analysis.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, truncated TrkB and TrkC isoforms were found (Cohen et al 1996;Kumar and deVellis 1996). A slightly different picture was reported by Kavanaugh et al (2000), where TrkC and TrkA were also demonstrated but with an increase of TrkA expression in more mature OL. A variation of the theme was noted by Robinson and Miller (1996) in that optic nerve OLP expressed TrkC, while those from the spinal cord did not.…”
Section: Oligodendrocytes Express Neurotrophin Receptorsmentioning
confidence: 75%
“…However, NTs are also protective in other conditions that cause oligodendroglial cell death. For example, NGF prevented TNF-α-mediated oligodendroglial cell death by activating the Akt pathway (Takano et al 2000) while NT-3 and, to a lesser extent, NGF protected the cells against AMPA-GluR-induced excitotoxicity at least partially (Kavanaugh et al 2000). It is interesting to note that AMPA does not induce a significant percentage of cell death of mature pig OL (Althaus et al, unpublished observation).…”
Section: Oligodendroglial Survival and Cell Death In Vitro And In Vivomentioning
confidence: 99%
“…Excitotoxicity in the oligodendroglial lineage is independent of NMDA receptors. Instead it is mediated by a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)/kainate receptors (Kavanaugh et al 2000, Matute et al 1997, McDonald et al 1998. These are the only ionotropic glutamate receptors expressed by this cell type (Figure 2) (McDonald et al 1998;Patneau et al 1994;Puchalski et al 1994).…”
Section: Ampa and Kainate Excitotoxicitymentioning
confidence: 99%
“…It has only recently been demonstrated that overstimulation of AMPA/kainate receptors causes excitotoxic damage in oligodendroglia in vitro and in vivo (Kavanaugh et al 2000;Matute et al 1997;McDonald et al 1998). Receptor-mediated cell death, which is induced by the activation of AMPA/kainate glutamate receptors, a¡ects exclusively the developing oligodendrocyte and can be prevented by speci¢c receptor antagonists (Follett et al 2004;Rosenberg et al 2003), highlighting a particular vulnerability of fetuses, neonates and infants to white-matter injury.…”
Section: Ampa and Kainate Excitotoxicitymentioning
confidence: 99%